Regulation of Human Pregnane X Receptor and its Target Gene Cytochrome P450 3A by Praeruptorin A Isolated from the Herbal Medicine Peucedanum praeruptorum - Huang, Ling; Bi, Hui-chang; Li, Yu-Hua; Zhang, Jun-Qing; Kuang, Shao-Yi; Zhang, Li; Wang, Yi-Tao; Huang, Min (Planta Medica, 2013)
Qianhu, the dried roots of Peucedanum praeruptorum, is a well-known traditional Chinese medicinal herb which was officially listed in the Chinese Pharmacopoeia. Praeruptorin A is the major active constituent of Qianhu. Our previous studies show that praeruptorin effectively transactivated the protein expression and catalytic activity of cytochrome P450 3A4 via the constitutive androstane receptor-mediated pathway. However, the effect of praeruptorin on the transactivation of cytochrome P450 3A4 through pregnane X receptor pathway is still unclear. To further elucidate the role of the pregnane X receptor pathway in the up-regulation of cytochrome P450 3A4 by praeruptorin, in this study, the effect of praeruptorin on the cytochrome P450 3A4 gene expression was investigated in mouse primary hepatocytes after knockdown of the pregnane X receptor by transient transfection of its siRNA; and the gene expression, protein expression, and catalytic activity of cytochrome P450 3A4 in the LS174T cells with pregnane X receptor overexpression were determined by real-time PCR, Western blot analysis, and LC-MS/MS-based cytochrome P450 3A4 substrate assay, respectively. We found that the level of cytochrome P450 3a11 gene expression in mouse primary hepatocytes was significantly increased by praeruptorin, but such an induction was suppressed after knockdown of pregnane X receptor by its siRNA. Praeruptorin significantly induced cytochrome P450 3A4 mRNA, protein expression, and functional activity through pregnane X receptor-mediated pathway in pregnane X receptor-overexpression LS174T cells; conversely, induction was not found in LS174T cells untransfected with pregnane X receptor plasmids. These findings suggest that praeruptorin can significantly up-regulate cytochrome P450 3A4 gene via the pregnane X receptor-mediated pathway, and this should be taken into consideration in potential herb-drug interactions.
Keywords: praeruptorin A; pregnane X receptor; cytochrome P450 3A; herb-drug interaction; Peucedanum praeruptorum; Apiaceae